Recon Marines - Voeller, Edward A; Marte, G. F. (Mankato, Minn. : Capstone Books, 2000)
Introduces the Marine Corps special forces known as the Recon Marines, describing their mission, history, and the equipment they use.
870L
Keywords: United States. -- Marine Corps; Special forces (Military science) -- United States; Scouts and scouting -- United States; Special forces (Military science)